Higher Education Students’ Reflective Journal Writing and Lifelong Learning Skills: Insights From an Exploratory Sequential Study - Alt, Dorit; Raichel, Nirit; Naamati-Schneider, Lior (Frontiers in Psychology, 2022)
Reflective journal (RJ) writing has been recognized as an effective pedagogical tool for nurturing students’ lifelong learning skills. With the paucity of empirical work on the dimensionality of reflective writing, this research sought to qualitatively analyze students’ RJ writing and design a generic reflection scheme for identifying dimensions of reflective thinking. Drawing on the theoretical scheme, another aim was to design and validate a questionnaire to measure students’ perceptions of their reflective writing experiences. The last aim was to quantitatively measure the link between perceived reflective writing and students’ tendency to use RJs in their future careers and personal lives. This exploratory sequential research included the following steps: First, experts’ review and analysis of 1312 RJ entries were attained. This step led to the design of a theoretical scheme of reflective writing and a 31-item questionnaire, used to gather data from 171 students (second-year pre-service teachers and third-year health managers). Partial Least Squares analysis corroborated the structure suggested by the theoretical scheme: two timelines–reflections regarding the current course assignments and those related to the student’s future development. Students’ tendency to use reflective skills in their future professional lives was highly connected to their long-term reflections, including learning experiences linked to academic, professional, personal, and multicultural development. The current study’s suggested validated generic scheme can be adapted and integrated into different curricula, thereby possibly increasing the potential of infusing RJ instructional strategies into higher education curricula, improving the quality of reflection in student journals, and promoting lifelong learning skills.